2020
DOI: 10.3389/fcell.2020.581674
|View full text |Cite
|
Sign up to set email alerts
|

Bcl11b/Ctip2 in Skin, Tooth, and Craniofacial System

Abstract: Ctip2/Bcl11b is a zinc finger transcription factor with dual action (repression/activation) that couples epigenetic regulation to gene transcription during the development of various tissues. It is involved in a variety of physiological responses under healthy and pathological conditions. Its role and mechanisms of action are best characterized in the immune and nervous systems. Furthermore, its implication in the development and homeostasis of other various tissues has also been reported. In the present revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 180 publications
0
5
0
Order By: Relevance
“…Previous studies have revealed that BCL11B is involved in the differentiation, proliferation and survival of multiple cell types [ 14 16 ]. BCL11B was also discovered to be expressed in mouse cochlear cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that BCL11B is involved in the differentiation, proliferation and survival of multiple cell types [ 14 16 ]. BCL11B was also discovered to be expressed in mouse cochlear cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…BCL11B -related disorder has been a recently reported hereditary disease caused by the BCL11B gene de novo variant. Up to now, there have been plenty of reports on the role of the BCL11B gene in the nervous and immune systems ( Arlotta et al, 2005 ; Li L. et al, 2010 ; Li P. et al, 2010 ; Kominami, 2012 ; Yu et al, 2015 ; Simon et al, 2016 , 2020 ; Fang et al, 2018 ; Daher et al, 2020 ), i.e., early studies demonstrate that Bcl11b plays a critical role in the development of corticospinal motor neurons axonal projections to the spinal cord in vivo by loss-of-function experiments in null mutant mice for Bcl11b ( Arlotta et al, 2005 ); on the other hand, Bcl11b was expressed in all T cell compartments and was indispensable for T lineage development and commitment in mice ( Li L. et al, 2010 ; Li P. et al, 2010 ). Those patients carrying the pathogenic variations of the BCL11B gene tend to have immune deficiency or intellectual developmental disorder, the major clinical manifestions are speech delay, dysmorphic facies, and T-Cell abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…The transcription factor BCL11B (B Cell Leukemia 11B), encoding Cys2-His2 zinc-finger protein transcription factor, is located on chromosome 14q32.2. BCL11B is broadly expressed and has critical functions in regulating multiple systems including the central nervous system, immune system, and skin ( 5 , 6 ). BCL11B contains three types of functional structures: six C2HH zinc-finger binding domains (ZnF1-6), one C2HC zinc-finger binding domain, and a NuRD interacting domain ( 7 ).…”
Section: Introductionmentioning
confidence: 99%